Development of triangular array eight patches antennas for circularly-polarized synthetic aperture radar sensor - Muhammad Fauzan Edy Purnomo; Vita Kusumasari; Edi Supriana; Rusmi Ambarwati; Akio Kitagawa (Universitas Ahmad Dahlan, 2020)
In this paper, we obtain the left-handed circularly polarized (LHCP) and right-handed circularly polarized (RHCP) of triangular array eight patches antennas using corporate feeding-line for circularly polarized-synthetic aperture radar (CP-SAR) sensor embedded on unmanned aerial vehicle (UAV) with compact, simple, and efficient configuration. Although the corporate feeding-line design has already been developed, its design was for the side antenna view of 0° and only produced one of LHCP or RHCP instead of both. Here, the design for LHCP and RHCP eight patches array fed by corporate feeding-line having the side antenna view of 36° at f=1.25 GHz for CP-SAR are discussed. We use the 2016 version of computer simulation technology (CST) to realize the method of moments (MoM) for analyzing. The performance results, especially for gain and axial ratio (Ar) at resonant frequency are consecutively 13.46 dBic and 1.99 dB both of LHCP and RHCP. Moreover, the 12-dBic gain-bandwidth and the 3-dB Ar-bandwidth of them are consecutively around 38 MHz (3.04%) and 6 MHz (0.48%). Furthermore, the two-beams appeared at boresight in elevation plane for average beamwidth of 12 dBic-gain and the 3 dB-Ar LHCP and RHCP have similar values of around 12° and 46°, respectively.